2016
DOI: 10.7439/ijasr.v2i4.3233
|View full text |Cite
|
Sign up to set email alerts
|

Concentration related differences in the inhibition of acetylcholinesterase activity in the common carp Cyprinus carpio by Phorate, an organophosphorous insecticide

Abstract: The activity of acetylcholinesterase (AChE) in the vital organs of fish such as gill, liver, muscle, kidney and brain of the freshwater common carp Cyprinus carpio (C. carpio) was investigated after exposing to acute lethal toxicity (ALT) and chronic sublethal toxicity (CST) of phorate. C. carpio fish were exposed to ALT (LC 50 /96 hours -0.71 ppm/l) of Phorate for one day and 4 days and CST (one-tenth of the LC 50 /96 hours -0.071 ppm/l) of Phorate for 1, 7, 15 and 30 days and the concentration related differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Our results agree with those reported for O. niloticus exposed to acute temperature shocks (Phrompanya et al 2021). It is suggested that tissue deterioration in specific brain regions may cause impairment of specific brain functions as well as changes in the physiological and behavioral processes of the fish, resulting in such behavioral changes as respiratory dysfunctions, loss of equilibrium, and erratic swimming (Lakshmaiah 2017).…”
Section: Resultssupporting
confidence: 91%
“…Our results agree with those reported for O. niloticus exposed to acute temperature shocks (Phrompanya et al 2021). It is suggested that tissue deterioration in specific brain regions may cause impairment of specific brain functions as well as changes in the physiological and behavioral processes of the fish, resulting in such behavioral changes as respiratory dysfunctions, loss of equilibrium, and erratic swimming (Lakshmaiah 2017).…”
Section: Resultssupporting
confidence: 91%
“…Deformations of the brain were evident, such as edema/ spongiosis, hemorrhage, enlargement of the SPV, and hydrops development. Similar alterations were observed in common carp exposed to different sizes of plastics (Hamed et al, 2022a), Channa punctatus exposed to the pesticide chlorpyrifos (Devi and Mishra, 2013), Gambusia affinis exposed to lead chloride (Alkshab and Taha, 2021), carp exposed to quinalphos (Chamarthi et al, 2014), carp exposed to organophosphate insecticide (Lakshmaiah, 2017), Catla catla exposed to heavy metals (Bose et al, 2015), and Carassius gibelio exposed to toxic cyanobacteria (Panagiotis et al, 2014).…”
Section: Figurementioning
confidence: 62%
“…Previous findings have also proved Phorate to be genotoxic on various other parameters, including the activities of carbohydrate metabolic enzyme, succinate dehydrogenase in common carp [14] and also altered protein content in various tissues of common carp [8]. Phorate also induced pronounced pathological toxicity in the brain of common carp, Cyprinus carpio and the extent of damage and degeneration were progressive with the exposure time period and the concentration of Phorate [16]. Phorate also has deleterious effects on humans as it causes cellular damage, as well as changes in DNA structure [7].…”
Section: Discussionmentioning
confidence: 92%
“…Various studies on the toxicity of Phorate on aquatic organisms, especially fish, have been carried out, confirming its toxicity and genotoxic role [13][14][15]. Histopathological toxicity of brain of Cyprinus carpio exposed to Phorate was also reported by Lakshmaiah, (2017) [16]. reported acute toxicity of Phorate on succinate dehydrogenase enzyme activity, which is an important enzyme for Krebs Cycle [17].…”
Section: Introductionmentioning
confidence: 82%